2022
DOI: 10.3389/fcell.2022.863825
|View full text |Cite
|
Sign up to set email alerts
|

Early Bioinformatic Implication of Triacidic Amino Acid Motifs in Autophagy-Dependent Unconventional Secretion of Mammalian Proteins

Abstract: Several proteins are secreted outside the cell, and in many cases, they may be identified by a characteristic signal peptide. However, more and more studies point to the evidence for an “unconventional” secretion, where proteins without a hitherto unknown signal are secreted, possibly in conditions of starvation. In this work, we analyse a set of 202 RNA binding mammalian proteins, whose unconventional secretion has recently been established. Analysis of these proteins secreted by LC3 mediation, the largest un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Incidentally, several parallel reports suggest the secretion of many RNA-binding proteins (~204) that are microtubule-associated protein light chain 3 (LC3)-mediated, and are termed as LC3-Dependent EV Loading and Secretion (LDELS; Leidal et al, 2020 ; Leidal and Debnath, 2020 ). In a recent extended study of these data sets, Biswal et al (2022) observed that of the 204 proteins, 202 of them were found to be leaderless and it has been suggested that the triacidic motif (EEE/DDD/DEE) is found to occur in a statistically significant proportion. The plausible role of phosphorylatable amino acid and the proximity of LC3-interacting region (LIR) in autophagy-dependent unconventional protein secretion has been reported.…”
Section: Rna-binding Propertymentioning
confidence: 99%
“…Incidentally, several parallel reports suggest the secretion of many RNA-binding proteins (~204) that are microtubule-associated protein light chain 3 (LC3)-mediated, and are termed as LC3-Dependent EV Loading and Secretion (LDELS; Leidal et al, 2020 ; Leidal and Debnath, 2020 ). In a recent extended study of these data sets, Biswal et al (2022) observed that of the 204 proteins, 202 of them were found to be leaderless and it has been suggested that the triacidic motif (EEE/DDD/DEE) is found to occur in a statistically significant proportion. The plausible role of phosphorylatable amino acid and the proximity of LC3-interacting region (LIR) in autophagy-dependent unconventional protein secretion has been reported.…”
Section: Rna-binding Propertymentioning
confidence: 99%